Classical Guidance to Prevent Academic Stress in Students of Mtsn 1 Palangka Raya City - Aisyah Nofin Nuraini; Asep Solikin (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Academic stress refers to the pressure and tension experienced by students in relation to academic performance and the educational environment, which can have an impact on students' psychology, physiology, and academic achievement. Appropriate techniques are needed to manage stress in order to help prevent situations that can have a negative impact on students. This study was conducted to (1) determine the difference in academic stress levels before and after the implementation of classical guidance and (2) determine the effectiveness of classical guidance in preventing academic stress among students at MTsN 1 Kota Palangka Raya. The population in this study was all 275 eighth-grade students at MTsN 1 Palangka Raya City, with a sample consisting of 31 students from class VIII-1, selected using purposive sampling. The results of the study show that: (1) before being given classical guidance services, most of the students in class VIII-1, namely 22 students, experienced moderate academic stress, 6 students experienced high academic stress, and 3 students experienced low academic stress. Meanwhile, after receiving classical guidance services, most students, namely 20 students, still experienced moderate academic stress, 6 students experienced high academic stress, and 5 students experienced low academic stress. The total pre-test score was 3893 and the post-test score was 3871. This means that there was not much change after the researcher provided classical guidance services; (2) the results of the hypothesis test using SPSS 25 software on the Paired Sample T Test method showed that the significance value obtained was 0.066. This indicates that the Sig value > 0.05, which indicates that classical guidance services are effective in preventing academic stress among students at MTsN 1 Kota Palangka Raya.